Turning the NARN into an ARC at the University of Bedfordshire: some reflections and comparisons - Arti Kumar (Association for Learning Development in Higher Education (ALDinHE), 2010)
In recent years I have increasingly been involved with action research at several levels (as a leader and participant on the NARN project and also on other institutional, collaborative and individual research studies). To fulfil my various responsibilities I convened and led the Action Research Consortium (ARC) at the University of Bedfordshire from June 2008 to June 2010. Evaluating the effects of this action provided a research topic and the context for my own personal and professional development, which I present in this paper as a reflective analysis. I focus on the main lessons learned and applied at a management level, through analysing the type of change ARC participants reported and discussed, and that I observed. My insights and recommendations are broadly informed by theories related to action research, Appreciative Inquiry and positive psychology approaches. I argue here that action research can generate continuous improvements in pedagogy - but achieving this ideal for all staff crucially depends on cycles of action research operating in a productive dynamic with their personal and professional development (and this could extend to students). This will not happen by chance, and has not happened as extensively as expected, even though my findings show that the opportunities offered through the ARC were motivating and beneficial for staff who engaged. For the potential impact of action research to be realised in the experience of practitioner-researchers and in the vision of universities, positive conditions must be created to support research-active programmes and communities, underpinned by congruent protocols and values. The recommendations I make here can help to promote and sustain an integral research culture and are therefore relevant to managers, as well as practitioners, who are doing, or thinking of embarking on, action research.